2012
DOI: 10.5535/arm.2012.36.6.762
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Mechanical Horseback Riding on Gait and Balance Ability in Stroke Patients

Abstract: ObjectiveTo investigate the therapeutic effects of mechanical horseback riding for gait and balance parameters in post-stroke patients.MethodThis study was a non randomized prospective positive-controlled trial over a 12 week period. From May 2011 to October 2011, 37 stroke patients were recruited from our outpatient clinic and divided into two groups. The control group received the conventional physiotherapy while the intervention group received the conventional physiotherapy along with mechanical horseback r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
62
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(67 citation statements)
references
References 33 publications
3
62
0
2
Order By: Relevance
“…The findings are in accordance with those of study that stroke patients performed horseback riding exercise for 35 min five times a week for eight weeks and Araújo8 ) in which elderly patients performed horseback riding exercise for eight weeks. They are also in accordance with the results of Han Jun-young16 ) in a study of stroke patients who performed horseback riding exercise for 12 weeks that an eight-week-long horseback riding exercise significantly improved the BBS scores of osteoarthritis patients. In general elderly, the average BBS score is 20.60 ± 4.0817 ) .…”
Section: Discussionsupporting
confidence: 90%
“…The findings are in accordance with those of study that stroke patients performed horseback riding exercise for 35 min five times a week for eight weeks and Araújo8 ) in which elderly patients performed horseback riding exercise for eight weeks. They are also in accordance with the results of Han Jun-young16 ) in a study of stroke patients who performed horseback riding exercise for 12 weeks that an eight-week-long horseback riding exercise significantly improved the BBS scores of osteoarthritis patients. In general elderly, the average BBS score is 20.60 ± 4.0817 ) .…”
Section: Discussionsupporting
confidence: 90%
“…A previous study reported that horse riding simulator treatment improved symmetrical weight-bearing in a standing posture, and improved balance through the maintenance of correct posture7 ) . A horse riding simulation exercise generates 50 to 100 three-dimensional physical movements (front and back, left and right, up and down) due to the movements of the horse riding exercise machine.…”
Section: Discussionmentioning
confidence: 98%
“…[7] Our robotic hippotherapy system is designed to facilitate stretching, rhythmic trunk rotation, core stabilization, strength, endurance, and cardiopulmonary function via the sensorimotor system (vestibular, proprioceptive). [2,6,[8][9][10][11] The system simulates live horse movements, including walking (6 km/h), trotting (15 km/h), cantering (25 km/h), and galloping (60 km/h). These movements are featured as exercise modes composed of 100 different two-dimensional movement patterns with 100 different exercise modes.…”
Section: Introductionmentioning
confidence: 99%
“…These movements are featured as exercise modes composed of 100 different two-dimensional movement patterns with 100 different exercise modes. Conceptually, robotic hippotherapy was developed based on the collective integration of the best clinical evidence [2,8,9] and the fact that pediatric neurorehabilitation must be fun, motivating, intensive, task-specific, rhythmic, repetitive, and integrated, and should be implemented over a long period of time to produce measurable changes in muscle size, [2,6] motor behavior, [10] and neuroplasticity. [11] Intensive repetitive, rhythmic movement is a hallmark of horse movement, like human locomotion.…”
Section: Introductionmentioning
confidence: 99%